Acute Appendicitis and Multisystemic Inflammatory Syndrome due to COVID-19: a Case Report and Literature Review - Hashlamoun, M.; Qafesha, R. M.; Salhab, R.Q; Huseein, B.M.; Benmelouka, A.Y; jobran, Afnan Waleed (AL-Kindy College Medical Journal, 2022)
The prevalence of gastrointestinal symptoms of COVID-19 is variable with different types of presentations. Some of them many present with manifestations mimicking surgical emergencies. Yet, the pathophysiology of acute abdomen in the context of COVID-19 remains unclear. We present a case of a previously healthy child who presented with acute appendicitis with multisystemic inflammatory syndrome. We also highlight the necessity of considering the gastrointestinal symptoms of COVID-19 infection in pediatric patients in order to avoid misdiagnosis and further complications.